Behavior of Highway Bridge PSC Girder with Different Support Arrangements Under Dynamic Loading - Akshay M. R; Amarnath B. V; Ramana, N. Venkata (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This article presents a detailed finite element analysis of a three-span PSC I-girder bridge using MIDAS Civil software. The primary objective is to investigate the structural behavior of the bridge girder under different support configurations, namely simply supported and continuous systems, combined with elastomeric Bearings and roller Supports. The analysis incorporates loading conditions as per IRC:6-2017, IRC: 112-2011, and IRC SP: 114-2018. The bridge model was subjected to IRC Class A and Class 70R vehicular loads, in addition to seismic loads, to evaluate critical performance parameters of deflections, bending moments, shear forces, torsional effects, and dynamic characteristics, such as natural periods, which were comprehensively studied. The results highlight that Continuous Girders with elastomeric bearings provide superior stiffness, reduced deflections, better control of torsion, and improved seismic performance compared to other configurations. The findings demonstrate that the selection of an efficient girder-support system plays a vital role in ensuring safety, serviceability, and resilience of medium to long-span PSC I-girder bridges.